Ovarian follicular dynamics of a creole cattle under grazing conditions in high Andean areas of Peru - Alfaro-Astorima, Miriam Ibet (2020)
Creole cattle are a potential resource to improve productivity in the high Andean zone of Peru; however, indiscriminate crossing with improved breeds is leading to the erosion of their genetic material. Studies of the physiological processes that govern its reproductive cycle are essential for the successful application of reproductive biotechnologies that ensure their preservation, use and subsequent dissemination. In order to study the follicular dynamics of creole cattle, 15 animals were evaluated under grazing conditions in two seasons of the year (rainy and dry). Follicular growth was evaluated by ultrasonographic monitoring, luteal activity by hormonal dosing, and proximal analysis of grass was performed by season. The average length of the estrous cycle was 21.39 ± 1.17 days for the rainy season and 22.07 ± 1.04 days for the dry season, with no statistical difference (p > 0.05). Cycles with 2 (16%), 3 (78%) and 4 (6%) follicular waves was observed. The maximum diameter of the ovulatory follicle reached was 17.11 ± 1.79 and 17.67 ± 1.21mm in the rainy and dry seasons, respectively. Of the 49 ovulations studied, 27 (55%) corresponded to the right ovary and 22 (45%) to the left ovary. There was no difference (p > 0.05) in growth rate or follicle diameter by season. The maximum diameter of the corpus luteum was 20.87 ± 1. 48 and 21.30 ± 1.86 mm with a growth rate of 1.01 ± 0.16 and 1.0 ± 0.15 mm/day. These results reflect the potential of creole cattle to maintain their cyclicity even in unfavorable environments.